2015
DOI: 10.1016/j.foreco.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem carbon (CO2 and CH4) fluxes of a Populus dettoides plantation in subtropical China during and post clear-cutting

Abstract: a b s t r a c tPoplar plantations have widely spread around the world due to its high productivity and adaptability. Clear-cutting is the primary harvesting method for poplar plantation management in southern China. However, the effect of harvesting on ecosystem carbon fluxes limits our ability to estimate its carbon sequestration. A consecutive, three-year observation on ecosystem CO 2 and CH 4 flux (F CO2 and F CH4 ) of a Populus dettoides plantation on the floodplain of Yangtze River was made prior and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Relatively few micrometeorological studies of CH 4 or N 2 O fluxes have been made in forest ecosystems in general [24][25][26][48][49][50][51][52][53]. Zona, Janssens [54] measured CO 2 , CH 4 and N 2 O fluxes above a short-rotation poplar plantation in Belgium, Gao, Chen [55] performed EC measurements of CO 2 and CH 4 in a poplar plantation in subtropical China and Mishurov and Kiely [56] did EC measurements of N 2 O fluxes on afforested grassland. We are not aware of any studies using simultaneous micrometeorological measurements of CO 2 , CH 4 and N 2 O at a clear-cut boreal forest stand.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few micrometeorological studies of CH 4 or N 2 O fluxes have been made in forest ecosystems in general [24][25][26][48][49][50][51][52][53]. Zona, Janssens [54] measured CO 2 , CH 4 and N 2 O fluxes above a short-rotation poplar plantation in Belgium, Gao, Chen [55] performed EC measurements of CO 2 and CH 4 in a poplar plantation in subtropical China and Mishurov and Kiely [56] did EC measurements of N 2 O fluxes on afforested grassland. We are not aware of any studies using simultaneous micrometeorological measurements of CO 2 , CH 4 and N 2 O at a clear-cut boreal forest stand.…”
Section: Introductionmentioning
confidence: 99%
“…Though it was shown that thinning increases soil CO 2 emissions by 29% (Zhang et al, 2018), another study suggests only a 6.8% increase (Yang et al, 2022). However, these two meta-analyses also reported that the responses of soil CO 2 emissions depend on numerous factors including thinning intensity, post-thinning recovery time, stand type, stand age, measurement season, local climate, thinning-induced changes in litterfall, root biomass, soil nutrients, soil microclimate, and soil microbial community composition and activities (Adamczyk et al, 2015;Gao et al, 2015;Hao et al, 2019;Keller et al, 2005;Zhang et al, 2018).…”
Section: Impact Of Stand Thinning On Soil Ghg Fluxesmentioning
confidence: 98%
“…One reason for this is that poplar has a high biomass accumulation rate [4] and is, therefore, used for the production of paper and wood products [5,6]. It is also increasingly used in green energy as it can be utilized to produce biofuels [7][8][9][10] and CO2 absorption to combat climate change [11,12]. In a number of cities around the world, it is used for urban landscaping [13,14], and its high resistance to heavy-metal pollution allows for it to be used for the phytoremediation of soils [15][16][17].…”
Section: Introductionmentioning
confidence: 99%